Paradigm, Ethics and Management (with regard to Social Responsibility) - Caravedo, Baltazar (2010)
This paper focuses on presenting social responsibility from the angle of ethics. The focus of this work is based on a descriptive analysis that allows us to understand the paradigm shift of corporate responsibility in its social context. Previously, the main objective of corporate social responsibility was the generation of competitiveness in the country. Nowadays, there are new conceptions of developing CSR. Consequently, the author will focus on social responsibility from a perspective of new ethics and this could be a transformative axis in favor of the population. Therefore, throughout the text it will be possible to appreciate how CSR is related to the concept of sustainable development since there is an economic, environmental and social baseline that requires lasting changes over time linked to the company. Second, there will be an important analysis of the reconfiguration of the new ethics in social responsibility. To this end, institutional decentralization and the promotion of internal leaderships that renew the pyramidal and vertical structure of companies will be highlighted. Third, the evolution of social responsibility in Peru framed from the 1970s to 1990, highlighting the historical background as the creation of National Business Conferences (CADE) and its speeches with a focus on CSR. And within that timeline a special emphasis will be made in the year 1992 given that the companies had a novel vision of social and political stability. Fourth, the other contributions will be mentioned, both at the legislative level and that of the Academy and that of Non-Governmental Organizations. In conclusion, the author reaffirmed how social responsibility can be approached from the point of view of ethics.